Thoracic surgeryComparison of the effects of pleurodesis induced by talc and hydrogen peroxide - Eser, Irfan; Gunay, Samil; Kurkcuoglu, Ibrahim Can (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Introduction: Pleural effusion occurs when fluid accumulates in the space between the parietal and visceral pleurae. It results either from increased production or decreased absorption of the fluid. It can arise from malignant or benign causes. The treatment for pleural effusions caused by malignant diseases is mainly palliative, with pleurodesis being the most frequently employed therapeutic method. The usage of chemical agents in pleurodesis causes inflammation which leads to adhesion of the pleural membranes. The aim of the study was to analyze the inflammatory effect of hydrogen peroxide (H 2 O 2 ) as a pleurodesis agent. Material and methods: The experimental study was conducted on 10 male New Zealand rabbits. In order to reduce the number of animals used in the experiment, both hemithoraces of the rabbits were used for pleurodesis. We divided the rabbits into two groups. In the first group, talc solution prepared in 0.9% saline was applied to the pleural cavities of both hemithoraces of 5 rabbits (a total of 10 pleural cavities), and, in the second group, a 3% hydrogen peroxide (H 2 O 2 ) solution prepared in 0.9% saline was applied to the pleural cavities of both hemithoraces of 5 rabbits (a total of 10 pleural cavities). Results: Blind macroscopic and microscopic examinations were carried out by a single pathologist using the scoring technique by Kaya et al. In macroscopic evaluation, grade 1 adhesion was found in the H 2 O 2 group only. Grade 2 adhesion was achieved in 4 pleural cavities in the H 2 O 2 group and 4 cases in the talc group. Grade 3 adhesion occurred in 3 cases in the H 2 O 2 group and 6 cases in the talc group. In microscopic examination, grade 1 adhesion took place in the H 2 O 2 group only. Grade 2 adhesion was achieved in 4 cases in the H 2 O 2 group and 1 case in the talc group. Grade 3 adhesion was found to be similar in both groups. On the other hand, talc was found to be superior to hydrogen peroxide in terms of providing grade 4 adhesion. Conclusions : It was determined that the use of talc in pleural cavities resulted in better grades of adhesion; however, H 2 O 2 was found to diffuse more homogeneously. H 2 O 2 is a chemical agent that has similar effects to talc in terms of pleurodesis, but demonstrates better diffusion on the pleural surfaces. It is also inexpensive, accessible, and easy to administer.